2017
DOI: 10.17761/1531-2054-27.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women who participated in a beta-test for an online-streamed yoga intervention after a stillbirth

Abstract: Background: Little is known about how to best care for mothers after stillbirth. As such, this paper will report the satisfaction and perceptions of an online yoga intervention (12-week beta test) in women after stillbirth. Methods: Participants (n=74) had a stillbirth within the last 24–months (M time since loss 9.65 ± 6.9 months). Post-intervention satisfaction surveys and interviews and dropout surveys were conducted. Descriptive statistics were used to analyze survey responses and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Some women mentioned feeling less self-conscious if practicing yoga at home (i.e., would not need to go out in public to attend a class). These experiences are not different from a small sample of predominately White women who experienced stillbirth and reported that they especially enjoyed the convenience and privacy of participating in yoga at their home [27]. One participant from this study indicated that online yoga at home might be even more attractive to the ethnic minority population, especially if a social option was included such as the option of participating with a friend.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Some women mentioned feeling less self-conscious if practicing yoga at home (i.e., would not need to go out in public to attend a class). These experiences are not different from a small sample of predominately White women who experienced stillbirth and reported that they especially enjoyed the convenience and privacy of participating in yoga at their home [27]. One participant from this study indicated that online yoga at home might be even more attractive to the ethnic minority population, especially if a social option was included such as the option of participating with a friend.…”
Section: Discussionmentioning
confidence: 70%
“…Women engaged in the online yoga videos for free. Selection criteria for the 30 yoga videos included the following: (1) videos that were used in our previous beta-testing [27] and were positively reviewed by mothers who experienced a stillbirth, (2) classes that were slower moving (i.e., beginner-based) with detailed instruction and alignment cues (i.e., safe and proper form), (3) classes that were safe for women up to 20-week gestation in the case a participant became pregnant during the intervention, and (4) videos that the research team believed would cultivate emotional regulation and self-compassion. For example, the research team considered evidence-based proposed mediators from a general population with post-traumatic stress, tone of the teacher (i.e., calming, accepting), commentary during the video (i.e., self-love, acceptance, being aware of emotions), and poses (e.g., forward fold, child’s pose, heart openers).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, given the ongoing COVID-19 pandemic and the cultural-shifts occurring around the acceptability of remotely-delivered programming, a web-based and scalable evidence-based intervention is increasingly relevant and critical. Even prior to the pandemic, web-based yoga programs have been found to be feasible and acceptable among various populations [e.g., ( 69 , 70 )]; however, little research has explored their effectiveness on improving body image and embodiment-related outcomes more specifically. Although there are many types of yoga practice, several yoga variations encompass mental health practices such as mindfulness (a key meditative component of yoga) and self-compassion [i.e., being non-judgmentally aware of experiences; ( 8 )].…”
Section: Introductionmentioning
confidence: 99%